Impact Of Political Policy On The Implementation Of Law Enforcement - Muhamad Romdoni; Santy Fitnawaty WN; Rizki Nurdiansyah (Pusdikra Publishing, 2022)
Enforcement law in Indonesia is still not yet walked with good and so concern. Problem enforcement law (law enforcement) always tends to inequality interaction dynamic Among aspect law in hope or das sollen, with aspect application law in the reality of the signal. In practice maintenance law in the field, there is sometimes a contradiction Between certainty law and justice. Writing this discusses the influence of politics on law enforcement in Indonesia. Politics and law are two things that affect each other. In enforcing the rule of law by institutions politics, the role of strength politics sitting in institutions politics is very decisive. When position law is more determined by politics, then activity political governed by and must be following rule law. The writer uses an approach to Socio-Legal studies, which is a study that sees law by merging Among analysis normative (norms law, juridical) and approach non-legal science. Socio-legal nature is prescriptive in that it gives solutions to problem law with a combined analysis of social normative and non-legal / aspect social approaches. Research results from this showing that politics heavily influence law in its formation. However, even though the law could not be separated from the element of political should when the law applies, all political activity must be subject to the law.